Motivation and Socially Embedded Career Development in Shaping Employee Engagement - Riana, Anggie Dilla; Mahdi, Irfan (Journal of Social Commerce, 2024)
This paper examines how career development and motivation can impact on engagement of employees in the public sector institutions and focuses on social mediation of such effects on development. Based on information acquired with the help of a well-designed survey tool and administered to civil servants; data that was then analyzed statistically by applying descriptive, correlational and inferential statistics, such as Pearson correlation and multiple linear regression, the results show a positive and robust value of motivation on the engagement in work with no statistically significant effect of career development. Nevertheless, the additional thematic interpretation indicates that this absence of statistical power can be explained by the deviance between the programmed developmental work and its social interpretation on social levels at the workplace. The paper talks about the centrality of social translation the way development programs are shared, justified and approved by peers and leaders in making career developing a social practice than a process. Motivation, on the same note, is also shown to be both a property of individuals and a process that is socially reinforced and more so in groups where there is common purpose, identification, and common cause. Such findings support the view that human resource strategies must be more than structural provisions, and the call is on socially resonant, culturally immersed, and relational vitality approaches to growth and interactions. The research adds to the set of theoretical and applied insights about the concept of employee engagement by redefining it as a socially constructed effect and especially applicable to digitally-mediated but interaction-heavy organization spaces.